Small molecule activation by mixed methyl/methylidene rare earth metal complexes. Issue 15 (14th March 2016) - Hong, Jianquan; Li, Zhenhua; Chen, Zhening; Weng, Linhong; Zhou, Xigeng; Zhang, Lixin
Abstract : Diverse reactivity patterns of mixed tetramethyl/methylidene rare-earth complexes bearing bulky benzamidinate coligands with PhCN, alkynes, and CS2 have been established and fully characterized. Abstract : Diverse reactivity patterns of mixed tetramethyl/methylidene rare-earth complexes bearing bulky benzamidinate coligands L3 Ln3 (μ2 -Me)3 (μ3 -Me)(μ3 -CH2 ) [L = [PhC(NC6 H3 i Pr2 -2, 6)2 ] − ; Ln = Y(1a ), Lu(1b )] with PhCN, alkynes, and CS2 have been established. Reaction of complexes1 with PhCN gave the μ3 -CH2 addition complexes (NCN dipp )3 Lu3 (μ2 -Me)3 (μ3 -Me)[μ–η 1 :η 1 :η 3 -CH2 C(Ph)N] [Ln = Y(2a ), Lu(2b )]. Treatment of complexes1 with phenylacetylene afforded unexpected alkenyl dianion complexes L3 Ln3 (μ2 -Me)3 (μ3 -Me)(μ–η 1 :η 3 -PhCCMe) [Ln = Y(3a ), Lu(3b )] through the insertion of rare earth methylidene into a C–H bond in a reductive fashion. However, reaction of complexes1 and HCCSiMe3 gave μ3 -Me protonolysis complexes L3 Ln3 (μ2 -Me)3 (μ3 -CCSiMe3 )(μ3 -CH2 ) [Ln = Y (4a ), Lu (4b )] in excellent yields. Treatment of complexes1 with CS2 led to the formation of the methyl activation complexes L3 Ln3 (μ2 -Me)2 (μ3 -CH2 )(μ3 –η 1 :η 2 :η 2 -S2 CCH2 ) [Ln = Y(5a ), Lu(5b )]. All the new complexes were fully characterized.